A facile one-step chemical synthesis of copper@reduced graphene oxide composites as back contact for CdTe solar cells. (15th November 2020) - Luo, Guangcan; Zhu, Linyu; Tan, Bo; Wang, Taowen; Bi, Xue; Li, Wei; Zhang, Jingquan; Hao, Xia; Wang, Wenwu; Zhang, Ziling
Graphical abstract: Highlights: A facile one-step chemical method was used for the synthesis of Cu@rGO composites. A Cu@rGO/Au system as a back contact layer was developed for the CdTe solar cells. rGO improves the hole collection ability, and supplies an active Cu diffusion source. Significantly enhanced performance (e.g., Eff  >  16%, Voc > 830 mV; FF > 73%) was achieved for CdTe solar cells. Abstract: The copper/reduced graphene oxide (Cu@rGO) composites have been synthesized via a novel and facile chemical method and been characterized by a series of measuring techniques. Then the Cu@rGO as a primary back contact has been coated on the absorber in the CdTe solar cells. After optimizing the Cu@rGO back contact processing, significantly enhanced performance especially in efficiency, open-circuit voltage and fill factor has been achieved for CdTe solar cells. The Cu@rGO supplies an effective Cu diffusion source after annealing which achieves a considerable hole concentration, and the rGO is converted into p-type conducting with Au metallization, resulting in the decrease of the back barrier and improvement of the hole collection ability. The cells with Cu@rGO/Au exhibit more outstanding photovoltaic performance than those with Cu/Au or rGO/Au back contact.